# Algebra Fail! - Simplifying squared terms.

• Mar 19th 2010, 06:04 PM
NeZVa
Algebra Fail! - Simplifying squared terms.
$(x+1/2)^2 - (x+3/2)^2$

How does it simplify... Is there a name for term of this nature? I've forgotten.
• Mar 19th 2010, 06:21 PM
harish21
Quote:

Originally Posted by NeZVa
$(x+1/2)^2 - (x+3/2)^2$

How does it simplify... Is there a name for term of this nature? I've forgotten.

$(x+1/2)^2 - (x+3/2)^2$
= ${(x^2)+2*x*\frac{1}{2}+[\frac{1}{2}]^2} - [(x^2)+2*x*[\frac{3}{2}]+[\frac{3}{2}]^2]$

= ${x^2}+x+\frac{1}{4}-{x^2}-3x-\frac{9}{4}$

= $-2x-\frac{8}{4}$

= $-2x-2$

= $-2(x+1)$
• Mar 19th 2010, 06:29 PM
harish21
Quote:

Originally Posted by harish21
$(x+1/2)^2 - (x+3/2)^2$
= ${(x^2)+2*x*\frac{1}{2}+[\frac{1}{2}]^2} - [(x^2)+2*x*[\frac{3}{2}]+[\frac{3}{2}]^2]$

= ${x^2}+x+\frac{1}{4}-{x^2}-3x-\frac{9}{4}$

= $-2x-\frac{8}{4}$

= $-2x-2$

= $-2(x+1)$

Remember: $(a+b)^2 = {a^2}+2ab+{b^2}$
• Mar 19th 2010, 06:49 PM
NeZVa
Quote:

Originally Posted by harish21
Remember: $(a+b)^2 = {a^2}+2ab+{b^2}$

Thanks, I had such a brain fart. ;)